Ligand-based surface engineering of nanomaterials: Trends, challenges, and biomedical perspectives - Ragini Singh; S.P. Srinivas; Mamta Kumawat; Hemant Kumar Daima (Elsevier, 2024)
Biomedical applications of nanomaterials, especially in diagnosing, management, and treatment of diseases are evolving. However, nanotoxicity remains a major challenge in availing the full biomedical potential of engineered nanomaterials. Nevertheless, recent advancements in the field have suggested that smart engineering of targeting ligands and presence of biomolecules on the surface of nanomaterials can reduce nanotoxicity through differential affinity, enhanced biocompatibility, and efficient internalization. Further, certain ligand-functionalized nanomaterials permit their tracking in cells and tissues over a prolonged period of time, making them suitable for nanomedicine applications. In this seminal review, a range of strategies, which have been employed for surface functionalization of nanomaterials using various biomolecules that confer amide / hydrazone bonds, thiol binding, and surface silanization have been evaluated. The challenges, and impact of surface functionalization of nanomaterials on cellular uptake, drug targeting, molecular imaging, and biocompatibility are also discussed. Finally, nanotoxicity aspects and recommendations of ligand-based surface engineered nanomaterials are detailed for future biomedical applications.